FLYPAPER EFFECT PADA BELANJA DAERAH PEMERINTAH PROVINSI DI PULAU SUMATRA - Nurhayati Nurhayati; Diana Septiana (Media Ekonomi, 2018)
The purpose of this study is to determine the phenomenon of the flypaper effect on the General Allocation Fund (DAU), Regional Original Income (PAD) on regional spending in provinces on the island of Sumatra. The dependent variable in this study is Regional Expenditure while the independent variable General Allocation Fund (DAU) and Local Original Revenue (PAD) flypaper effect phenomenon is a condition when the government responds to more spending by using balance funds rather than using Local Original Revenue (PAD). This study uses panel data analysis Multiple Linear Regression analysis tools. The population of this study is all regions in the province of Sumatra, which consists of 10 provinces with a total sample of 50 regions on the island of Sumatra over a 5-year period from 2014-2018. The results showed that Local Original Revenue and General Allocation Fund in general had a positive effect on regional expenditure on the island of Sumatra. However, judging by Local Original Revenue province has a positive influence on regional spending only in the provinces of Lampung, Riau, South Sumatra, North Sumatra and Aceh. Whereas General Allocation Fund has a positive influence on regional spending only in the provinces of North Sumatra and South Sumatra. This study also concluded that in general there was a flypaper effect on provinces on the island of Sumatra because the Local Original Revenue (PAD) coefficient value was smaller than General Allocation Fund (DAU).